Content generation for patient-reported outcome measures for retinal degeneration therapeutic trials. (3rd July 2020) - Lacy, Gabrielle D.; Abalem, Maria Fernanda; Popova, Lilia T.; Santos, Erin P.; Yu, Gina; Rakine, Hanan Y.; Rosenthal, Julie M.; Ehrlich, Joshua R.; Musch, David C.; Jayasundera, K. Thiran
ABSTRACT: Purpose: Generate content for a patient-reported outcome (PRO) measure for use in future clinical trials for inherited retinal degenerations. Methods: Patients at the University of Michigan Kellogg Eye Center with a clinical diagnosis of inherited retinal degeneration with varying phenotypes were recruited for interviews. First, in-depth interviews were performed to solicit a wide range of patient experiences pertaining to visual function. Coders qualitatively analyzed the transcripts from these interviews using Atlas.ti software (Version 8.1.3 (522)) to draft questionnaire items. Next, the questionnaire was tested and refined based on participant feedback in cognitive interviews and administrator feedback in the pilot survey administration (pilot interviews). Results: A total of 55 participants with a clinical diagnosis of inherited retinal degeneration were interviewed throughout the three study phases: in-depth interviews (n = 26), cognitive interviews (n = 16), and pilot interviews (n = 13). Coded items were analyzed for frequency of occurrence and related themes, then organized into common domains. Within each domain, PRO items were drafted to address the functional limitations or adaptations experienced by patients. Conclusions: Items for a PRO measure have been drafted and evaluated for interpretability in the target inherited retinal degeneration patient population. Content validity for the items was established through a process of in-depth interviews, cognitive interviews, and pilot interviews.